An Analysis of Educational Values in “Totto-Chan: The Little Girl at the Window” by Tetsuko Kuroyanagi Based on Paulo Freire’s Perspective - Jamaluddin Jamaluddin; Abd. Ghofur (PANYONARA: Journal of English Education, 2020)
The novel "Totto Chan: The Little Girl at the Window" is a novel in which some parts of its story reflect the concept of education that is unique and different. The concept of education in this novel related to an educational value according to Paulo Freire’s perspective. Therefore, this research is mainly purposed to search about what are the educational values found in "Totto Chan: The Little Girl at the Window"? and how educational values appear in "Totto Chan: The Little Girl at the Window" based on Paulo Freire’s perspective? This research is a qualitative one by using the content analysis method. Two data sources were chosen, the primary data source is the novel its-self and the secondary data are books, literature, official websites, and other relevant materials. In general, the result found 52 educational values contained in the novel, and 28 educational values based on Paulo Freire’s perspective. Those are divided into 6 points: liberating education, pedagogy of the oppressed, dialogic education, the concept of conscientization, contextual education and critical education. Through this research, it is expected that teachers can implement the positive things that exist in this study and in the novels at school and also encourage students’ interest in literature.